Mediacja jako metoda rozwiązywania konfliktów międzynarodowych - Bibiluri, Megi (Kultura-Społeczeństwo-Edukacja, 2016)
The presented article is aimed at reflecting usage of mediation as a form of international conflicts settlement and at revealing its factors, at the example of the case of conflict in Abkhazia, Georgia. The article is a hypothesis on to what extend international or regional organizations act as effective mediators during mediation process. Attempt of conflict regulation and work of the mediation platform created after Russian-Georgian war are discussed. The theory discussing main variables for evaluating international mediation represented in mediation literature have been used for evaluating mediation factors. The article shows the level of mediation effectiveness in international conflicts, when it is not clear which are the conflicting sides; it shows that when there is an influential country, considering its capabilities, it has enough power to act as effective mediator, only in case if it does not have direct interest in the conflict. We have concluded that mediation can be effective only when it is clear which the conflicting sides are. It is considered that international organizations cannot be effective in conflict resolution when a conflict is in cold phase.